Smart load management of water injection systems in offshore oil and gas platforms integrating wind power. Issue 9 (24th July 2017) - Sanchez, Santiago; Tedeschi, Elisabetta; Silva, Jesus; Jafar, Muhammad; Marichalar, Alexandra
Abstract : The pollution coming from the use of gas turbines (GTs) in oil and gas (O&G) platforms requires greener solutions. One option is to use wind turbines (WTs) to supply the water injection systems (WISs) and explore smart energy management to make the O&G sector more sustainable. The effect of WT integration, and their the coordination with the local GTs, needs to be carefully analysed since the intermittency of the wind can jeopardise the stability of the offshore grid. The existence of flexible loads (FLEX) interfaced by variable speed drives (VSD), such as WISs, can help overcome the challenges related to wind intermittency and rotor angle stability: suitable control of such non‐essential loads can be implemented to reduce the effect of wind power fluctuations, balance power generation and consumption and contribute to the optimal efficiency of the GT adjusting its loading conditions. This work investigates the system dynamics under short‐term wind‐induced power fluctuations, analysing the evolution of electrical variables, such as active power and generator rotor speed, to evaluate the possible arise of low‐frequency oscillations. The impact of an adequate WIS load control to increase the system damping is also explored and an algorithm for system damping estimation is proposed.